THE ACHIEVEMENT OF GENRE PARAGRAPH WRITING ABILITY OF HIGH SCHOOL STUDENTS ASSESSED THROUGH INTENSIVE AND RESPONSIVE WRITING ASSESSMENT - I Komang Budiarta (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2021)
Writing is one of language skills that is the most difficult skill to be mastered. This skill should be taken into account in teaching learning process. The English teachers at high schools in Badung, Gianyar and Denpasar gave writing test to their students by using a test that provided some topics which made the students difficult to imagine, develop their ideas and sometimes the test was not appropriate for their students’ writing level. The present research was intended to figure out the achievement and the quality of the genre paragraph which was assessed by administering intensive and responsive writing assessment. The present research used an ex-post facto research design. The samples of the present study were taken from 16 schools in the aforementioned three regencies. The obtained data were then analyzed by means of norm-reference measure of five standard values. The result showed that 71% of the samples were successful; meanwhile, 29% of the samples were unsuccessful in writing genre paragraph which was assessed by administering intensive and responsive writing assessment. In addition, the quality of their genre paragraphs was mainly good, but the needed extra effort on narrative.